Design and Build a Wedding Organizer Using a User Centered Design Approach - Muhammad Ikbal Ernanto; Muhamad Ariandi (Budapest International Research and Critics University, 2022)
Constraints that are often experienced by brides and grooms in determining wedding decorations and the type of clothing to be worn must of course match or match the desired decoration with the lack of information that can be used as a reference in making decisions regarding wedding preparations and wedding receptions. in accordance with the existing costs (budget). Currently, the system used by the Baba wedding organizer family still uses a manual system where the process must come directly to the place. Of course, this is an obstacle in sharing information and existing processes because it cannot be done by businesses all the time. To overcome this problem, it is necessary to create an information system, namely the Wedding Organizer Ordering Information System using the User Centered Design (UCD) Approach Method, a method in a design design that focuses on user needs. In relation to Information Systems, User Centered Design is part of the SDLC (System Development Life Cycle), so that the design of applications developed through UCD will be optimized and focused on the needs of end-users so that it is hoped that applications that will follow the needs of users and users do not need to change behavior. to use the app. The UCD approach will be used as the basis for the Baba Family website design. The software development method used is the User Centered Design method. This website-based wedding organizer information system uses the Codeigniter framework and the programming languages PHP, HTML, CSS, Javascript and MySQL Database Management System (DBMS).